Strategi Musyrif Tahfizh dalam Meningkatkan Pencapaian Hafalan Al-Qur’an pada Santri di Ma’had Tahfizhul Qur’an - Abdur Rahman; Sukari; Pebri Azhari (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The achievement of Qur’an memorization often encounters obstacles, particularly those related to mentoring that requires the active role of musyrif tahfizh. This study aims to analyze the strategies employed by musyrif tahfizh in improving students’ memorization achievement at Ma’had Tahfizhul Qur’an (MATIQ) Isy Karima using a descriptive qualitative approach through a case study. Data were collected through interviews, observations, and documentation, and then analyzed using data reduction, data presentation, and inductive conclusion drawing. The results show five strategic roles of the musyrif tahfizh, namely as a facilitator, learning manager, demonstrator, mentor, and motivator. The synergy of these roles creates an effective, holistic, and sustainable tahfizh learning ecosystem. These findings have the potential to serve as a mentoring model for other tahfizh institutions; however, the study is limited to a single institution, a limited number of informants, and a specific time frame, so generalization remains limited.